Mathematical skills in Prader-Willi Syndrome. - Bertella L; Girelli L; Grugni G; Marchi S; Molinari E; Semenza C (Journal of Intellectual Disability Research, 2005)
This paper investigates mathematical skills in Prader-Willi Syndrome (PWS), a pathological condition because of congenital alterations of chromosome pair 15. The following questions were addressed: (1) Are mathematical skills in PWS relatively more impaired with respect to other cognitive functions (as has been repeatedly but anecdotally reported)?; and (2) What is the nature of the mathematical impairment?The first study employed the Wechsler Adult Intelligence Scale (WAIS) and an extensive battery of cognitive tasks for which norms are known. Both batteries include a mathematical section. The second study used a theoretically motivated series of mathematical tasks specifically designed to individually assess the different cognitive components underlying mathematical skills.Mathematical skills were found to be the most impaired cognitive abilities together with short-term memory capacity. No specific mathematical domain was seen to be unaffected in PWS participants. The clearest deficits observed concern'syntactic' processes in number transcoding, multiplication, number facts retrieval and calculation procedures.Failure of mathematical skills is the most distinctive feature in the cognitive profile of PWS. However, to determine whether this is indeed a specific pattern of performance related to PWS, results must be compared with those obtained with patients manifesting other genetic disorders.